(untitled) (Journal of Engineering, 2009)
The objective of this research is to present the numerical analysis of deep foundation system namely controlled modulus columns (CMC) for support of embankments. This paper describes the analysis modeling used for CMC foundation system using the finite element method. The elasto-plastic finite element model used to simulate the embankment soil foundation has been verified against field data. The results obtained from this study showed that the effect of CMC could be negligible when the soil strength increased in terms of its angle of internal friction. With low values of internal friction angle, the CMC reduce the potential of surface deformation about 12%. The values of surface deformation decreased with column diameter until it reach constant value at (0.5m) where less than this values the reduction in deformation could be negligible or have insignificant effect. The maximum deformation was observed at the middle of embankment, also the deformation at the embankment foundation reduce by about (17%) when take into consideration the CMC in soil embankment foundation.